Pregnant patients undergoing cholecystectomy: nationwide assessment of clinical characteristics and outcomesAJOG Global Reports at a Glance - Genevieve R. Mazza, MD; Ariane C. Youssefzadeh, MD; Laurel S. Aberle, MD; Zachary S. Anderson, MD; Rachel S. Mandelbaum, MD; Joseph G. Ouzounian, MD, MBA; Kazuhide Matsushima, MD; Koji Matsuo, MD, PhD (Elsevier, 2024)
BACKGROUND: Gallstone disease in pregnancy is one of the most common indications for nonobstetrical surgery during pregnancy. National-level data on contemporary surgical practice and outcomes are limited. OBJECTIVE: This study aimed to assess the clinical characteristics and outcomes of patients undergoing cholecystectomy during pregnancy. STUDY DESIGN: This cross-sectional study examined the Healthcare Cost and Utilization Project's 2 nationwide databases in the United States: the National Inpatient Sample and the Nationwide Ambulatory Surgery Sample. The study population included 18,630 patients who had cholecystectomy during pregnancy from January 2016 to December 2020. The exposure was gestational age, grouped sequentially into the following 5 groups: first trimester (<14 weeks), early second trimester (14-20 weeks), late second trimester (21-27 weeks), early third trimester (28-36 weeks), and late third trimester (≥37 weeks). The main outcomes were clinical demographics, medical comorbidities, surgical information, and pregnancy characteristics and outcomes, assessed by gestational age. RESULTS: Cholecystectomy was most common in the early second trimester (32.1%), followed by the first trimester (25.2%), late second trimester (23.1%), early third trimester (12.4%), and late third trimester (7.2%). Patients in the first-trimester group were more likely to be aged ≥35 years, to smoke, and to have acute cholecystitis, severe hyperemesis gravidarum including metabolic disturbance, pregestational diabetes, multifetal gestation, and sepsis/shock (P<.001). Patients in the early-third-trimester group were more likely to be obese and have gestational diabetes, Charlson Comorbidity Index of ≥1, premature rupture of membranes, and intrauterine growth restriction, whereas those in the late-third-trimester group were more likely to have gallstone pancreatitis, biliary colic, chorioamnionitis, gestational hypertension, preeclampsia, and severe maternal morbidity including sepsis (P<.001). At the cohort level, a laparoscopic approach was used in most cholecystectomy procedures (97.5%), and bile duct injury was uncommon (<0.1%). Delivery during the admission occurred in 0.3%, 0%, 0.6%, 17.8%, and 60.6% in the 5 gestational age groups, respectively (P<.001). Among the cases that had delivery in the early- and late-third-trimester groups, the delivery event preceded cholecystectomy in 61.4% and 86.2%, respectively, whereas both delivery and cholecystectomy occurred on the same day in 34.3% and 13.8%, respectively. CONCLUSION: This nationwide analysis suggests that clinical and pregnancy characteristics and outcomes of patients undergoing cholecystectomy differ by pregnancy stage with a bimodal distribution. Although patients in the first and third trimesters have distinct medical conditions, more clinically significant pregnancy and maternal outcomes were found in both groups compared with patients in the second trimester.